Preparing medical students for the e-patient*. (3rd July 2017) - Masters, Ken
Abstract: The emergence of the e-patient has resulted in many medical practitioners' being ill-equipped to deal with the 21st-century medical practice. This Guide is a teaching guide for medical educators so that they can prepare their students for the new environment that has resulted from the emergence of the e-patient. Within the context of theoretical perspectives, the Guide begins by defining the concept, and examining the history of the e-patient, detailing typical e-patient activities and some complexities raised by these activities. Finally, the Guide details the topic areas that should be covered in a course aimed at preparing medical students for e-patients. The result is a theoretical and practical teaching Guide that equips medical teachers and their students with the necessary background information, and also assists teachers in the teaching of that information so that their students may become health practitioners fully equipped to deal with the problems and potential of the e-patient.